Yield potential expression of soybean genotypes - Júnior, Hugo Motta Navarro; Costa, José Antonio (Pesquisa Agropecuaria Brasileira, 2002)
Soybean has high yield potential, which is not totally expressed due to genotype vs. environment interaction. Six soybean genotypes of different maturity groups were used with the objective of studying their yield potential expression and quantifying it during ontogeny. The experiment was conducted during the 1996/97 growing season in the Agronomic Experimental Station of the Universidade Federal do Rio Grande do Sul, Eldorado do Sul, RS, Brazil. Plants were evaluated individually from flowering until maturity. Results obtained indicate that high yield potential does not necessarily mean an efficient plant in reproductive structure retention. Yield potential estimated in the flowering and beginning of grain filling stages are not maintained until maturity. Genotypes with high yield potential in the R8 stage do not present the highest yield potential in the R2 and R5 stages, but the lowest differences between potential estimated in the R5 stage and the one estimated in the R2 stage.
Keywords: Glycine max; grain; ontogeny; yield components